Consumer Acceptance Of Internet Banking Among Penangities, Malaysia - Wooi, Ong Ai (2009)
The research on acceptance or adoption of internet banking has not been throughly investigated in Malaysia. Hence, the purpose of this study is to investigate the level of consumer awareness and the attitudinal factors that influence on the acceptance of Internet banking among Malaysian consumers.